فاعلية برنامج الإلكتروني في تنمية المهارات العملية للشرائح الالكترونية لمقرر الدوائر الإلكترونية لدى طلاب الصف الثاني الثانوي الصناعي - خليل، محمد السيد السيد محمد; إسماعيل، مجدي إبراهيم; صالحة، رشا نبيل سعد إبراهيم (جامعة الزقازيق - كلية التربية, 2024)
هدف البحث إلي دراسة أثر استخدام برنامج إلكتروني في تنمية المهارات العملية للشرائح الإلكترونية لدى طلاب الصف الثاني الثانوي الصناعي بمادة الدوائر الإلكترونية تخصص الإلكترونيات والكمبيوتر، حيث تكونت عينة البحث من (٥٠) طالب بالصف الثاني الثانوي الصناعي تخصص الإلكترونيات والكمبيوتر، وقسمت العينة إلى مجموعتين إحداهما تجريبية (٢٥ طالباً) والأخرى ضابطة (٢٥ طالباً)، وقد تم التدريس لطلاب المجموعة التجريبية باستخدام برنامج إلكتروني، في حين تم التدريس لطلاب المجموعة الضابطة باستخدام الطريقة التقليدية، وتم تطبيق أدوات البحث وهي: اختبار تحصيلي لقياس الجانب المعرفي المرتبط بالاتجاهات العملية وبطاقة ملاحظة لقياس الجانب الأدائي المرتبط بالمهارات العملية للشرائح الإلكترونية في "الباب الأول دوائر التغذية بالقدرة الكهربية والباب الثاني دوائر المكبرات" بمادة الدوائر الإلكترونية. وقد كشفت نتائج البحث عن: وجود فرق ذا دلالة إحصائية عند مستوي (٠,٠١) بين متوسطي درجات طلاب المجموعتين التجريبية والضابطة لصالح طلاب المجموعة التجريبية في التطبيق البعدي للاختبار التحصيلي، ووجود فرق ذا دلالة إحصائية عند مستوي (٠,٠١) بين متوسطي درجات طلاب المجموعتين التجريبية والضابطة لصالح طلاب المجموعة التجريبية في التطبيق البعدي لبطاقة الملاحظة. The aim of the research was to study the effect of using an electronic program on the development of practical skills in electronic circuits for second-year industrial secondary school students specializing in electronics and computers. The research sample consisted of 50 students in the second year of industrial secondary school, specializing in electronics and computers. The sample was divided into two groups: an experimental group (25 students) and a control group (25 students). The experimental group received instruction using an electronic program, while the control group received instruction using traditional methods. The research tools used were: a achievement test to measure the cognitive aspect related to practical skills in electronic circuits, and an observation card to measure the performance aspect related to practical skills in electronic circuits in the topics of "Power Supply Circuits" and "Amplifier Circuits" in the subject of electronic circuits. The research results revealed the following: There was a statistically significant difference at the 0.01 level between the mean scores of the experimental group and the mean scores of the control group in favor of the experimental group in the post-test application. There was a statistically significant difference at the 0.01 level between the mean scores of the experimental group and the mean scores of the control group in favor of the experimental group in the post-observation card application. There was a positive correlation between the mean scores of the achievement test and the mean scores of the students' performance in the observation card for practical skills in the experimental group.
Keywords: التعليم المهني -- المقررات الدراسية -- البرامج الرقمية -- المهارات العملية -- الشرائح الإلكترونية -- طلبة المدارس